2008
DOI: 10.1515/zna-2008-7-810
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Boronizing on the Radiation Shielding Properties of Steel

Abstract: The radiation shielding properties of steel and its variation with the boronizing process have been investigated. For this purposes the linear attenuation coefficients of steel have been measured before and after boronizing the steel at the photon energy of 662 and 1250 keV. The measured results before boronizing were compared with the theoretical calculation. It was clearly seen that boronizing improved the radiation shielding properties of steel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…From this figure, we say that the μ increases with increasing Ni content due to changing the of borided Fe-Ni binary alloys. The same results for μ have been reported in the other studies [5,6]. They showed that attenuation coefficient depends on the chemical composition of materials.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…From this figure, we say that the μ increases with increasing Ni content due to changing the of borided Fe-Ni binary alloys. The same results for μ have been reported in the other studies [5,6]. They showed that attenuation coefficient depends on the chemical composition of materials.…”
Section: Resultssupporting
confidence: 86%
“…The studies showed that the degree to which gamma radiation is attenuated is dependent upon the energy of the incident gamma radiation, the atomic number and density of the elements in the shielding material, and the thickness of the shielding [1][2][3][4][5][6]. Carbon steels or stainless steels, as lead (Pb), have been commonly used as materials for thermal and radiation shields [2,3,[7][8][9].…”
Section: Introduction:-mentioning
confidence: 99%
See 1 more Smart Citation